BASIC PROBLEMS AND CHALLENGES IN MODERN TRANSLATION - Bakhtiyorovich, Ilkhamov Bokhodir (Journal of Higher Education and Academic Advancement, 2024)
Globalization profoundly impacts not only the cultural landscapes of nations but also their linguistic systems, resulting in increasingly complex translation challenges. General Background: As languages evolve and intermingle due to global interactions, the demand for accurate and culturally sensitive translations escalates. Specific Background: Traditional translation methods often struggle to keep pace with rapid linguistic changes, particularly when aided by artificial intelligence (AI) translators, which can misinterpret cultural nuances and idiomatic expressions. Knowledge Gap: Despite advancements in AI-driven translation technologies, there remains a significant gap in understanding how these systems can be optimized to enhance translation quality and effectiveness in a globalized context. Aims: This study aims to explore innovative strategies and methodologies that can improve translation outcomes, focusing on the interplay between globalization and language evolution. Results: Through a comprehensive analysis of existing translation frameworks and the incorporation of interdisciplinary approaches, the findings reveal critical factors that contribute to more accurate and contextually appropriate translations. Novelty: The research introduces a novel model that integrates cultural competence into AI translation algorithms, addressing specific shortcomings in current technologies. Implications: The implications of this study extend beyond the field of translation studies; they inform AI development, enhance cross-cultural communication, and support global interactions in diverse fields such as business, diplomacy, and education. This work ultimately aims to contribute to the creation of more effective and culturally aware translation tools in an increasingly interconnected world.